Assessing the Impact of 10 years of FTA Research: a synthesis of the 5 integrated impact studies - Coccia, Federica; Rouge, J-C.; Claus, R.; Davel, R.; Hughes, K.; Pinto, D.; Gotor, Elisabetta; Jones, S.; Thuerer, T.; Rachman, R.; Wakesho, G.; Nijbroek, R.; et al. (CGIAR Research Program on Forests, Trees and Agroforestry, 2022)
In 2021, the CGIAR Research Program on Forests, Trees and Agroforestry (FTA) completed a set of studies, under the guidance and oversight of its Independent Steering Committee (ISC), to document its progress in addressing five key global challenges. These studies had the following purposes: (i) to design a workable approach and operational method to assess impacts at scale at the level of the FTA program, since 2011; (ii) to deploy the method effectively on a set of five identified development challenges addressed by FTA; (iii) to learn lessons from the exercise for FTA post 2021. This document provides a synthesis of the five studies and draws lessons and recommendations for research for development programs.